2020
DOI: 10.1111/jgs.16933
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association Between Hearing Loss, Vision Loss, Dual Sensory Loss, and Cognitive Decline

Abstract: BACKGROUND/OBJECTIVES To better understand the role of sensory loss as a potentially modifiable risk factor for cognitive decline, this study examined cognitive decline in relation to single modality hearing or vision loss and dual sensory loss. DESIGN Longitudinal secondary data analysis. SETTING The Health and Retirement Study (HRS) and its supplement: The Aging, Demographics, and Memory Study (ADAMS). PARTICIPANTS Individuals aged 73 and older (N = 295). MEASUREMENTS Hearing loss was defined by an inability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 52 publications
1
31
0
1
Order By: Relevance
“…In truth, hearing loss can significantly affect the trajectory of healthy aging through precipitating physical and mental health outcomes, such as falls and disabilities, frailty, loneliness, depression, social isolation, and beyond (7)(8)(9)(10)(11)(12)(13). In particular, emerging evidence indicates a connection between ARHI and higher risk of cognitive decline in older people (14)(15)(16)(17)(18)(19), and hearing loss has markedly been acknowledged as a major modifiable risk factor for dementia and Alzheimer's Disease (AD) (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In truth, hearing loss can significantly affect the trajectory of healthy aging through precipitating physical and mental health outcomes, such as falls and disabilities, frailty, loneliness, depression, social isolation, and beyond (7)(8)(9)(10)(11)(12)(13). In particular, emerging evidence indicates a connection between ARHI and higher risk of cognitive decline in older people (14)(15)(16)(17)(18)(19), and hearing loss has markedly been acknowledged as a major modifiable risk factor for dementia and Alzheimer's Disease (AD) (20).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we analyzed the core data from the 2016 Health and Retirement Study (HRS) (36). Although prior studies were carried out regarding the hearing-cognition association with the HRS cohort (16,19,37), few of them provided outcome data disaggregated by sex or gender. Our aim was to investigate how gender-related characteristics affect the hearing-cognition association in the older demographic alongside biological sex.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the coincidence of vision and hearing impairment further increases the risk of falls (40). In addition, it leads to restricted daily activity (42) and is associated with increased risk for mild cognitive impairment (43) and faster cognitive decline (44).…”
Section: Discussionmentioning
confidence: 99%
“…A null relationship between VI and cognitive change was also reported in 4 other longitudinal studies. 25,[50][51][52] For example, Hong et al 51 performed a prospective, population-based study of 3,654 participants of the Blue Mountains Eye Study in Australia and reported that VI was not associated with a ≥ 3 point decline in MMSE-Blind scores over 5 years (OR 0.84; 95% CI 0.40-1.79) or 10 years (OR = 1.09; 95% CI 0.52-2.30). This is in contrast to 4 longitudinal studies and one meta-analysis that have found a relationship between VI and cognitive function [12][13][14]53,54 and 1 study that found a relationship between visual acuity, used as a continuous variable, and cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, if sensory loss is thought to cause disuse of the brain leading to atrophy then perhaps people with dual vision and hearing impairments would be at an even higher risk of cognitive decline, as has been indicated in the literature. 25 The Canadian Longitudinal Study on Aging (CLSA) is a large, population-based cohort study with data on over 30,000 middle-aged and older adults. 26 The CLSA used 5 cognitive tests that did not require vision.…”
Section: Introductionmentioning
confidence: 99%